(untitled) (Research, Society and Development, 2022)
Popularly identified as official-of-room or false-weed, Asclepias curassavica L. is an annual, latent, erect, small plant, whose height, depending on environmental conditions, varies between 40 and 80 cm. Pasture weed, considered highly toxic to cattle, although it also has medicinal properties, it is frequently used to kill worms and, in moderate doses, is purgative. The study and formation of a crop begins with the production of seedlings, and the quality of the propagation material is decisive. At the same time, during the storage period, it is essential to control both the physiological and sanitary quality of the seed. Pre-hydration is usually a procedure adopted to harmonize emergence, especially in wild seeds. The objective was, at present study, to evaluate hydration times in the moisture gain and vigor of the seeds, using a randomized block design, with three replications, in which the treatments corresponded to a 4 x 2 factorial arrangement, resulting from the combination of the factors of time of hydration (zero, two, four, and six hours) and seed age (newly harvested; two years old) in the wild species oficial de sala. In the germination pattern, young and old seeds behaved little differently in terms of hydration times. Seed hydration contributes to harmonizing germination and, for six hours, it allows germination of around 84% in new seeds, being innocuous in old seeds, which proved to be unviable.